THE EFFECT OF ANTICIPATION GUIDE STRATEGY ON THE ELEVENTH GRADE STUDENTS’ READING COMPREHENSION OF SMAN 3 PEKANBARU - Kiki Andriyani; Rumiri Aruan; Eliwarti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This pre-experimental research aimed to find out the significant effect of Anticipation Guide Strategy to the eleventh grade studens’ reading comprehension of SMAN 3 Pekanbaru. More than 50% students of SMAN 3 Pekanbaru often face some problems in comprehending the text caused by some factors such as: lack of background knowledge, lack of vocabulary, the technique in teaching reading comprehension, and students’ background knowledge which has not been activated. To overcome the problems, the writer used Anticipation Guide Strategy in teaching and learning process. The population was the eleventh grade students of SMAN 3 Pekanbaru, while the sample class was XI IPS 2. The writer used cluster sampling technique to decide the sample and the instrument of this research was test in the form of multiple choice. The test included five aspects of reading comprehension which are; main idea, inference, reference, factual information, and vocabulary, and three aspects of narrative text which are; generic structure, purpose, and language features. The students’ reading comprehension scores were analyzed using t-test formula. The writer used the level of significance at 0.05 (5%). After being calculated, the value of t-observed was 6.549, whereas the value of t-table on the df (degree of freedom) 33 was 2.021. Therefore, the alternative hypothesis that there is a significant effect of Anticipation Guide Strategy on students’ reading comprehension of SMAN 3 Pekanbaru was accepted and its null hypothesis was rejected. In conclusion, using Anticipation Guide Strategy has a significant effect on students’ reading comprehension of SMAN 3 Pekanbaru.Keywords: Anticipation Guide Strategy, Reading Comprehension2